Nietzsche’s perspectivism and comprehension - Araujo de Sousa, Mauro (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
Nietzsche’s perspectivism points to an infinite amount of perspectives. to the myriad of points of view on the same subject, to the achievement of a better comprehension of something and new possibilities of interpretation. In this essay, the path to a comprehension of the most relevant aspects of Nietzsche’s proposal is paved by the analysis and synthesis of the conceptos from Nietzsche’s philosophy, aiming to stress the viability of a perspectivated comprehensive epistemology of Communication.